ASPEK PERPAJAKAN ATAS PENGENDALIAN BIAYA OPERASIONAL TERHADAP EFISIENSI PENGELUARAN KAS - Tjandra Wasesa; Sugiharto Sugiharto; Bambang Karnaen P. (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
Each unit of business activity certainly has the desire to continue to grow. Therefore efforts to increase sales as a step to achieve revenue targets must be planned properly, as well as optimal control of costs incurred for business operations, so that cash assets used to pay operational costs must be controlled.One of the efforts to control operational costs is by paying attention to the taxation aspects related to operational expenses which cannot be charged as a deduction from business income. So it can be concluded that it becomes a consideration for companies to pay attention to the taxation aspect of controlling operational costs in order to achieve the efficiency of company cash disbursements.